Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.cell.2015.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Synaptic Input Fields of Neurons with Super-Resolution Imaging

Abstract: Summary As a basic functional unit in neural circuits, each neuron integrates input signals from hundreds to thousands of synapses. Knowledge of the synaptic input fields of individual neurons, including the identity, strength and location of each synapse, is essential for understanding how neurons compute. Here we developed a volumetric super-resolution reconstruction platform for large-volume imaging and automated segmentation of neurons and synapses with molecular identity information. We used this platform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(112 citation statements)
references
References 67 publications
(89 reference statements)
3
109
0
Order By: Relevance
“…6). A recent 4-color 3D STORM study of synaptic input fields in retinal interneurons confirmed the suitability of mouse retinal samples for such studies (Sigal et al, 2015). …”
Section: Evolution Of Methods For Studying Rod Cell Structurementioning
confidence: 79%
“…6). A recent 4-color 3D STORM study of synaptic input fields in retinal interneurons confirmed the suitability of mouse retinal samples for such studies (Sigal et al, 2015). …”
Section: Evolution Of Methods For Studying Rod Cell Structurementioning
confidence: 79%
“…STORM imaging of Bassoon and the glutamate receptors GluR1 and GluR2 was also achieved in 4% paraformaldehyde‐fixed mouse brain tissue . A combination of immunohistochemistry for the synaptic scaffolding protein gephyrin, with transgenic expression of the fluorophores GFP and YFP, was performed in mouse retinal sections . This permitted detailed structural imaging of pre‐and postsynaptic domains in glycinergic and GABAergic synapses within the retina.…”
Section: Discussionmentioning
confidence: 99%
“…This permitted detailed structural imaging of pre‐and postsynaptic domains in glycinergic and GABAergic synapses within the retina. The tissue preparation protocol included refinements such as post‐fixing with glutaraldehyde and epoxy resin embedding followed by ultra‐thin sectioning (70 nm) . Similar protocols have been used for mitochondrial labelling in 10–20 μm sections of mouse brain, heart and kidney .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, improved automated or semi-automated techniques have been developed for in vitro and in vivo quantification of synapses using fluorescence microscopy (Ippolito and Eroglu 2010; Schätzle et al 2012; Dumitriu et al 2012; Busse and Smith 2013; Fogarty et al 2013; Danielson and Lee 2014; Sanders et al 2015; Klenowski et al 2015; Sigal et al 2015). The combination of fluorescence microscopy, immunolabeling of key pre- and postsynaptic markers of excitatory/inhibitory synapses and automated software analysis, has afforded new high-throughput methodology allowing for rapid quantification of putative neurochemical synapses.…”
Section: Introductionmentioning
confidence: 99%